Supported MWW molecular sieve composite material as well as preparation method and application thereof
By loading epoxy-modified polyethyleneimine on the MWW molecular sieve, the problem of poor carbon dioxide adsorption performance in the prior art is solved, efficient carbon dioxide selective adsorption is achieved, and the demand for carbon dioxide capture by climate change is met.
Patent Information
- Application Number
- CN202311293171.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-08
AI Technical Summary
The prior art does not perform well in carbon dioxide adsorption, especially under high temperature conditions, with limited load capacity and adsorption capacity, making it difficult to meet the demand for carbon dioxide capture by climate change.
The MWW molecular sieve is used as a carrier to support the epoxy compound modified polyethyleneimine, which significantly improves the performance of selective adsorption of carbon dioxide by enhancing the degree of branching and opening of the chain segments.
It significantly improves the selective adsorption performance of carbon dioxide, improves the adsorption amount and load, especially in medium-temperature conditions, and has a wide range of application prospects.
Smart Images

Figure CN119771361A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molecular sieve composite material and a preparation method and application thereof, and belongs to the field of carbon dioxide gas adsorption, separation and purification. Background Art
[0002] The concentration of carbon dioxide in the atmosphere continues to rise, leading to a series of problems such as climate change. To meet this challenge, the international community reached a consensus on carbon reduction and emission reduction through the United Nations Climate Change Conference. Carbon dioxide capture, utilization and storage (CCUS) as one of the solutions has attracted more and more attention from researchers and the industry. Among them, solid adsorption separation has broad development prospects as one of the important technical solutions for CCUS due to its advantages such as low regeneration energy consumption, easy equipment construction and moderate output.
[0003] Previous studies have shown that when polyethyleneimine is loaded onto a porous carrier SBA-15 to prepare a solid adsorbent, its carbon dioxide adsorption capacity at 40°C is only increased to 1.5 mmol / g, and when it is increased to 55°C, it only reaches 2.9 mmol / g (Catalysis Today, 2012, 194, 44-52). Some researchers have also loaded ethylenediamine onto H-type Y molecular sieves. Although the obtained composite material has good stability, the carbon dioxide adsorption capacity at 40°C does not exceed 1.9 mmol / g, and the actual effect is not ideal (Energy Environ. Sci., 2016, 9, 1803-1811). The flaky morphology and layered structure provide better development potential to a certain extent. CN104437418B discloses a layered material loaded with polyethyleneimine and a preparation method thereof. The layered silicate material loaded with polyethyleneimine can be prepared by a one-pot method under the conditions of silicon source, heteroatom source and alkaline substance. However, due to the limitation of synthesis conditions, the loading amount of polyethyleneimine is not high, and the improvement of carbon dioxide adsorption is limited. Therefore, the development of an adsorbent with strong selective carbon dioxide adsorption ability has important positive significance. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a supported MWW molecular sieve composite material and a preparation method and application thereof. The composite material of the present invention exhibits excellent performance in the selective adsorption of carbon dioxide.
[0005] The inventors have found through research that when MWW molecular sieve is used as a carrier to load polyethyleneimine modified with epoxy compounds, the degree of branching of the polymer chain segments is enhanced. When loaded onto the MWW molecular sieve with a lamellar structure, the chain segments are not easily folded due to hydrogen bonds, thereby stretching the chain links of the active amine groups, fully exposing the alkaline adsorption sites, and significantly improving the performance of selective adsorption of carbon dioxide.
[0006] The first aspect of the present invention provides a supported MWW molecular sieve composite material, comprising an MWW molecular sieve and a supported epoxy compound-modified polyethyleneimine. Based on the mass of the composite material, the content of the epoxy compound is 0.5% to 28.0%, preferably 10.0% to 28.0%, and the content of the polyethyleneimine is 5.0% to 48.0%, preferably 25.0% to 45.0%.
[0007] Furthermore, based on the mass of the composite material, the content of the epoxy compound is 0.5% to 28.0%, preferably 10.0% to 28.0%, for example 2%, 5%, 10%, 13%, 14%, 18%, 20%, 22%, 26%, 28%, etc., and any value in the range formed by any two of these values.
[0008] Furthermore, based on the mass of the composite material, the content of polyethyleneimine is 5.0% to 48.0%, preferably 25.0% to 45.0%, for example 5%, 10%, 15%, 20%, 25%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, etc., and any value in the range formed by any two of these values.
[0009] Furthermore, the loaded MWW molecular sieve composite material, based on the mass of the composite material, has a mass content of MWW molecular sieve of 24.0% to 90.0%, preferably 25.0% to 55.0%, for example, 24%, 29%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 55%, 60%, 70%, 80%, 90%, etc., and any value in the range formed by any two of these values.
[0010] Further, the MWW molecular sieve includes at least one of SCM-1, SCM-2, SCM-6, MCM-22, MCM-49, etc., preferably SCM-1. Among them, SCM-1 and SCM-2 are specifically recorded in CN104511271B, and SCM-6 is specifically recorded in CN105217651B.
[0011] Furthermore, the specific surface area of the MWW molecular sieve is 30 to 1000 m2 / g, preferably 300 to 700 m2 / g.
[0012] Furthermore, the average molecular weight of the polyethyleneimine is 300 to 100,000, preferably 500 to 10,000.
[0013] Furthermore, the epoxy compound is one or both of propylene oxide and 1,2-butylene oxide.
[0014] The second aspect of the present invention provides a method for preparing the composite material, comprising: using MWW molecular sieve material as a carrier, loading epoxy compound-modified polyethyleneimine onto the carrier, and drying to obtain the composite material.
[0015] Furthermore, the MWW molecular sieve includes at least one of SCM-1, SCM-2, SCM-6, MCM-22, MCM-49, etc. The MWW molecular sieve material exists in the form of, but is not limited to, the original powder obtained by direct synthesis, or the product after one-step calcination to remove the template.
[0016] Furthermore, the method for loading the polyethyleneimine modified by the epoxy compound onto the carrier adopts an impregnation method. The carrier is impregnated with an impregnation solution of polyethyleneimine modified by the epoxy compound, and a composite material is obtained after drying. Among them, the preparation method of the impregnation solution of polyethyleneimine modified by the epoxy compound comprises: dissolving polyethyleneimine in a solvent to prepare an impregnation solution, then adding the epoxy compound dropwise, stirring for 10 to 480 minutes, preferably 30 to 300 minutes, to obtain an impregnation solution. The solvent is selected from one or more of methanol, ethanol, isopropanol, butanol, cyclohexanol, acetone, water, etc. In the impregnation solution, the mass concentration of the epoxy compound and polyethyleneimine is 0.05% to 36%, preferably 1% to 25%.
[0017] Furthermore, the immersion temperature is 1 to 50°C, preferably 15 to 40°C, and more preferably 20 to 30°C.
[0018] Furthermore, the immersion time is 3 to 120 hours, preferably 6 to 72 hours.
[0019] Furthermore, after the impregnation reaction is completed, the drying method can obtain the corresponding product by vacuum heating drying, the temperature can be 40-150°C, more preferably 50-130°C, the drying time can be 2-50h, preferably 3-24h, and the solvent extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0020] The third aspect of the present invention provides the use of the composite material in carbon dioxide adsorption.
[0021] Furthermore, the application includes: a gas containing carbon dioxide is brought into contact with the composite material to obtain purified gas.
[0022] Furthermore, in the carbon dioxide-containing gas, the volume content of carbon dioxide is 0.04% to 60% by volume, and other gases include at least one of nitrogen, methane, carbon monoxide, hydrogen, etc.
[0023] Furthermore, the adsorption conditions are as follows: adsorption temperature is 10-85°C, preferably 40-75°C, pressure is 0.01-100 kPa, time is 1-60 min, volume space velocity is 5-2400 h -1 .
[0024] Furthermore, when the MWW molecular sieve composite material of the present invention is used for the selective adsorption of carbon dioxide gas, it can be regenerated through multiple cycles, and the regeneration conditions are: without heating or heating, the heating temperature is 40-150°C, preferably 60-130°C, using at least one of nitrogen, carbon dioxide gas, water vapor, or the tail gas after adsorption separation and purification, to purge the composite material to achieve regeneration, or regeneration is achieved by decompression degassing.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] The MWW molecular sieve composite material of the invention uses the MWW molecular sieve as a carrier and carries polyethyleneimine modified with epoxy compounds, and has excellent performance of selectively absorbing carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The carbon dioxide gas adsorption-desorption isotherms of the molecular sieve composite material obtained in Example 1 and the porous silica composite material obtained in Comparative Example 1 at 40° C. are shown in FIG.
[0028] Figure 2 The carbon dioxide gas adsorption-desorption isotherms of the molecular sieve composite material obtained in Example 2 and the porous silica composite material obtained in Comparative Example 2 at 40° C. are shown in FIG.
[0029] Figure 3 This is a scanning electron microscope image (SEM) of the molecular sieve composite material obtained in Example 1;
[0030] Figure 4 This is a scanning electron microscope image (SEM) of the molecular sieve composite material obtained in Example 2;
[0031] Figure 5 is the carbon dioxide atmosphere thermogravimetric analysis curve of the molecular sieve composite material obtained in Example 1;
[0032] Figure 6 This is the carbon dioxide atmosphere thermogravimetric analysis curve of the silicon dioxide composite material obtained in Comparative Example 1. DETAILED DESCRIPTION
[0033] According to the present invention, the molecular sieve composite material obtained above can be used in any physical form, such as powder, granule or molded product (such as strip, clover, etc.). These physical forms can be obtained in any conventional manner known in the art without particular limitation.
[0034] In the context of this specification, including in the following examples and comparative examples, the model of the scanning electron microscope (SEM) of the molecular sieve and its composite material is S-4800II field emission scanning electron microscope.
[0035] In the context of this specification, including in the following examples and comparative examples, the thermogravimetric analysis instrument for molecular sieves and their composite materials is the American TA Instrument SDT Q600, and the test adopts carbon dioxide (≥99.99%) and nitrogen (≥99.999%) atmospheres (switched separately) at 100-200 mL / min.
[0036] In the context of this specification, including in the following examples and comparative examples, the specific surface area and pore structure characterization of the molecular sieve and its composite material is measured by nitrogen physical adsorption and desorption method (BET method): the nitrogen adsorption and desorption isotherms of the molecular sieve and its composite material at 77K are measured using an adsorption analyzer (Microtrac BELSORP max II adsorption instrument), and then calculated by the BET equation and t-plot equation; the carbon dioxide adsorption capacity of the molecular sieve and its composite material is characterized by the carbon dioxide gas adsorption and desorption isotherms: measured by the volume method, the carbon dioxide adsorption and desorption isotherms of the molecular sieve and its composite material at 0-40°C are measured using an adsorption analyzer. The experimental conditions for the molecular sieve and its composite material are: the measurement temperature is -169°C (i.e. 77K, the nitrogen adsorption and desorption are tested at the boiling point of liquid nitrogen to use the BET method) or 0-40°C (accurate adjustment can be achieved by circulating water bath temperature control), and the molecular sieve composite material is vacuum pretreated at 100-150°C for 4-6 hours before measurement.
[0037] The present invention is further described in detail below using examples, but the present invention is not limited to these examples.
[0038] Example 1
[0039] 1.00 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 6 g of anhydrous methanol, stirred to make it uniformly dissolved, and then 0.587 g of 1,2-butylene oxide was added dropwise, and stirred for 60 minutes to complete the reaction to form a uniform impregnation solution. Then, calcined SCM-1 molecular sieve powder (prepared in the same manner as in Example I-1 of CN104511271B, with a specific surface area of 520 m 2 / g) 1.00 g, stirred to make it completely dispersed and continued stirring in 25°C air for 24 hours. After completion, it was placed in a vacuum drying oven at 50°C for 5 hours to obtain the product MWW molecular sieve composite material. The solvent methanol extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0040] Example 2
[0041] Dissolve 1.50 g of polyethyleneimine (purity 99wt%, average molecular weight 600) in 8 g of anhydrous methanol, stir to make it evenly dissolved, then drop 0.8805 g of 1,2-butylene oxide, stir for 45 minutes to complete the reaction, and form a uniform impregnation solution. Then add 1.00 g of SCM-1 molecular sieve powder (same as Example 1) after calcination, stir to make it completely dispersed and continue to stir in 20°C air for 32 hours. After completion, place it in a vacuum drying oven at 50°C for 6 hours to obtain the product MWW molecular sieve composite material, and the solvent methanol extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0042] Example 3
[0043] 1.00 g of polyethyleneimine (purity 99 wt%, average molecular weight 1800) was dissolved in 5 g of anhydrous methanol and 1 g of anhydrous ethanol, stirred to make it evenly dissolved, then 0.350 g of 1,2-butylene oxide was added dropwise, stirred for 90 minutes to complete the reaction and form a uniform impregnation solution. Then, the calcined SCM-6 molecular sieve powder (prepared in the same manner as in Example 1 of CN105217651B, with a specific surface area of 394 m 2 / g) 1.00 g, stirred to make it completely dispersed and continued stirring in air at 30-35°C for 12 hours. After completion, it was placed in a vacuum drying oven at 50°C for 8 hours to obtain the product MWW molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0044] Example 4
[0045] 1.00 g of polyethyleneimine (purity 99wt%, average molecular weight 1800) was dissolved in 6 g of anhydrous methanol and 3 g of anhydrous ethanol, stirred to make it evenly dissolved, and then 0.650 g of 1,2-butylene oxide and 0.150 g of propylene oxide were added dropwise, and stirred for 40 minutes to complete the reaction to form a uniform impregnation solution. Then 0.50 g of the calcined molecular sieve SCM-1 powder (same as Example 1) and 0.50 g of SCM-6 powder (same as Example 3) were added, stirred to make it completely dispersed and stirred continuously in air at 25-30°C for 18 hours. After completion, it was placed in a vacuum drying oven at 60°C for 8 hours to obtain the product MWW molecular sieve composite material, and the solvent extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0046] Example 5
[0047] 3.00 g of polyethyleneimine (purity 99wt%, average molecular weight 600) was dissolved in 16 g of anhydrous methanol, stirred to make it evenly dissolved, and then 1.761 g of 1,2-butylene oxide was added dropwise, and stirred for 120 minutes to complete the reaction to form a uniform impregnation solution. Then 2.00 g of SCM-1 molecular sieve powder (same as Example 1) after calcination was added, stirred to make it completely dispersed and continued to stir in 20°C air for 32 hours. After completion, the product was placed in a vacuum drying oven at 60°C for 9 hours to obtain the product MWW molecular sieve composite material, and the solvent extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0048] Example 6
[0049] Dissolve 2.00 g of polyethyleneimine (purity 99wt%, average molecular weight 600) in 15 g of anhydrous methanol, stir to make it evenly dissolved, then drop 1.174 g of 1,2-butylene oxide, stir for 50 minutes to complete the reaction, and form a uniform impregnation solution. Add 2.00 g of calcined SCM-1 molecular sieve powder (same as Example 1), stir to make it completely dispersed and continue to stir in 30°C air for 48 hours. After completion, place the product in a vacuum drying oven at 60°C for 18 hours to obtain the product MWW molecular sieve composite material, and the solvent extracted by vacuum can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0050] Example 7
[0051] 0.6667 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 5 g of anhydrous methanol and 3 g of isopropanol, stirred to make it evenly dissolved, and then 0.391 g of 1,2-butylene oxide was added dropwise, and stirred for 75 minutes to complete the reaction to form a uniform impregnation solution. Then, the calcined MCM-22 molecular sieve powder (preparation method is the same as that of the literature Chinese Journal of Catalysis, 2020, 41, 1062-1066, specific surface area 450 m 2 / g) 1.00 g, stirred to make it completely dispersed and continued stirring in 30°C air for 24 hours. After completion, the product was placed in a vacuum drying oven at 60°C for 18 hours to obtain the product MWW molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0052] Example 8
[0053] 1.00 g of polyethyleneimine (purity 99wt%, average molecular weight 600) was dissolved in 6 g of anhydrous methanol, stirred to make it uniformly dissolved, and then 0.2556 g of propylene oxide was added dropwise, and stirred for 60 minutes to complete the reaction to form a uniform impregnation solution. Then 1.00 g of SCM-1 molecular sieve powder (same as Example 1) after calcination was added, stirred to make it completely dispersed and continued to stir in 25°C air for 24 hours. After completion, it was placed in a vacuum drying oven at 50°C for 5 hours to obtain a product MWW molecular sieve composite material, and the solvent methanol extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0054] Example 9
[0055] 0.6667 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 5 g of anhydrous methanol and 3 g of isopropanol, stirred to make it evenly dissolved, and then 0.391 g of 1,2-butylene oxide was added dropwise, and stirred for 75 minutes to complete the reaction to form a uniform impregnation solution. Then, the calcined MCM-49 molecular sieve powder (preparation method is the same as that of the literature Chinese Journal of Catalysis, 2020, 41, 1062-1066, specific surface area 450 m 2 / g) 1.00 g, stirred to make it completely dispersed and continued stirring in 30°C air for 24 hours. After completion, the product was placed in a vacuum drying oven at 60°C for 18 hours to obtain the product MWW molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0056] Comparative Example 1
[0057] The process was the same as in Example 1 except that the carrier used for impregnation was 1.00 g of porous silica.
[0058] The porous silica was prepared by the following method: 900 g of water, 95 g of silica aerogel, and 5 g of 30 wt% silica sol were mixed and stirred evenly, and then ground with a colloid mill and injected as a spray-dried sample. The injection rate was 30 ml / min, the air inlet temperature was 210°C, and the porous silica crude product was obtained by spray drying, and then calcined at 550°C to obtain the porous silica.
[0059] Comparative Example 2
[0060] The process was the same as in Example 2 except that the carrier used for impregnation was 1.00 g of porous silica.
[0061] The preparation method of porous silica is the same as that of Comparative Example 1.
[0062] Comparative Example 3
[0063] 1.00 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 6 g of anhydrous methanol, stirred to make it uniformly dissolved, and then 1.00 g of calcined SCM-1 molecular sieve powder (same as in Example 1) was added, stirred to make it completely dispersed and continued to stir in air at 25°C for 24 hours. After completion, it was placed in a vacuum drying oven at 50°C for 5 hours to obtain the product MWW molecular sieve composite material.
[0064] Comparative Example 4
[0065] 0.6667 g of polyethyleneimine (purity 99wt%, average molecular weight 600) was dissolved in 5 g of anhydrous methanol and 3 g of isopropanol, and stirred to make it evenly dissolved to form a uniform impregnation solution. Then 1.00 g of calcined MCM-22 molecular sieve powder (same as Example 7) was added, stirred to make it completely dispersed and continued to stir in 30°C air for 24 hours. After completion, the product was placed in a vacuum drying oven at 60°C for 18 hours to obtain the product MWW molecular sieve composite material, and the solvent extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0066] Comparative Example 5
[0067] 0.6667 g of polyethyleneimine (purity 99wt%, average molecular weight 600) was dissolved in 5 g of anhydrous methanol and 3 g of isopropanol, and stirred to make it evenly dissolved to form a uniform impregnation solution. Then 1.00 g of calcined MCM-49 molecular sieve powder (same as Example 9) was added, stirred to make it completely dispersed and continued to stir in 30°C air for 24 hours. After completion, the product was placed in a vacuum drying oven at 60°C for 18 hours to obtain a product MWW molecular sieve composite material, and the solvent extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0068] Table 1 Composition and adsorption results of the composite materials obtained in each case
[0069]
[0070]
[0071] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A supported MWW molecular sieve composite material, comprising an MWW molecular sieve and a supported epoxy compound-modified polyethyleneimine, wherein the content of the epoxy compound is 0.5% to 28.0%, preferably 10.0% to 28.0%, and the content of the polyethyleneimine is 5.0% to 48.0%, preferably 25.0% to 45.0%, based on the mass of the composite material.
2. The composite material according to claim 1, characterized in that The supported MWW molecular sieve composite material has a mass content of MWW molecular sieve of 24.0% to 90.0%, preferably 25.0% to 55.0%, based on the mass of the composite material.
3. The composite material according to claim 1, characterized in that The MWW molecular sieve includes at least one of SCM-1, SCM-2, SCM-6, MCM-22, and MCM-49; preferably, the specific surface area of the MWW molecular sieve is 30 to 1000 square meters per gram, preferably 300 to 700 square meters per gram.
4. The composite material according to claim 1, characterized in that The average molecular weight of the polyethyleneimine is 300 to 100,000, preferably 500 to 10,000; and / or the epoxy compound is one or both of propylene oxide and 1,2-butylene oxide.
5. A method for preparing the composite material according to any one of claims 1 to 4, comprising: The MWW molecular sieve material is used as a carrier, polyethyleneimine modified with an epoxy compound is loaded on the carrier, and a composite material is obtained after drying.
6. The preparation method according to claim 5, characterized in that: The method for loading the epoxy compound-modified polyethyleneimine onto the carrier adopts an impregnation method, wherein the preparation method of the epoxy compound-modified polyethyleneimine impregnation solution comprises: dissolving polyethyleneimine in a solvent to prepare an impregnation solution, then dropwise adding the epoxy compound, stirring for 10 to 480 minutes, preferably 30 to 300 minutes, to obtain an impregnation solution; Preferably, in the impregnation solution, the mass concentration of the epoxy compound and the polyethyleneimine is 0.05% to 36%, preferably 1% to 25%; Preferably, the immersion temperature is 1 to 50°C, preferably 15 to 40°C, more preferably 20 to 30°C; Preferably, the immersion time is 3 to 120 hours, preferably 6 to 72 hours.
7. The preparation method according to claim 5, characterized in that: The drying is carried out by vacuum heating drying at a temperature of 40 to 150° C., preferably 50 to 130° C., and a drying time of 2 to 50 hours, preferably 3 to 24 hours.
8. Use of the composite material according to any one of claims 1 to 4 in carbon dioxide adsorption.
9. The use according to claim 8, characterized in that: The application includes: a gas containing carbon dioxide is contacted with the composite material to obtain a purified gas; in the gas containing carbon dioxide, the volume content of carbon dioxide is 0.04% to 60% by volume, and other gases include at least one of nitrogen, methane, carbon monoxide, hydrogen, etc.
10. The use according to claim 8 or 9, characterized in that: Adsorption conditions are as follows: temperature 10-85°C, preferably 40-75°C, pressure 0.01-100 kPa, time 1-60 min, volume space velocity 5-2400 h -1 .
Citation Information
Patent Citations
Layered material loaded with polyethyleneimine and its preparation method
CN104437418B
A molecular sieve, its manufacturing method and its application
CN104511271B
SCM-6, aluminosilicate molecular sieve, its synthesis method and applications
CN105217651B
Polyethyleneimine-loaded Magadiite layered material and preparation method thereof
CN104437417A
Method for removing carbon dioxide in high-purity gas
CN114522504A